The Effects of Resection Technique on Implant Migration in Single Radius Posterior-Stabilized Total Knee Replacement - Teeter, Matthew G.; Perry, Kevin; Yuan, Xunhua; Howard, James L.; Lanting, Brent A. (The Journal of Knee Surgery, 2020)
The purpose of the present study was to measure the effects of gap balancing and resection techniques on migration of a single total knee replacement implant design. A total of 23 patients (24 knees) were recruited on referral to either a surgeon performing gap balancing or a surgeon performing measured resection and followed prospectively. All patients received a fixed bearing, posterior stabilized total knee replacement implant of a single radius femoral component design with cement fixation, and all aspects of care outside of resection technique were identical. Patients underwent radiostereometric analysis (RSA) at 2 weeks (baseline), 6 weeks, 3 months, 6 months, 1 year, and 2 years. Migration of the tibial and femoral components was compared between groups. Tibial component migration was greater at 2 years in the gap balancing group (mean difference = 0.336 mm, p = 0.036), but there was no difference at 1 year. One measured resection and three gap balancing tibial components demonstrated continuous migration > 0.2 mm between years 1 and 2. There was no difference in femoral component migration. Small differences in tibial component migration were found between the gap balancing and measured resection techniques. However, comparing the migration to established predictive thresholds for long-term loosening risk, implants performed with both techniques were found to have equally low revision risk.
Keywords: total knee arthroplasty; gap balancing; measured resection; radiostereometric analysis; implant migration